2022
DOI: 10.1111/poms.13655
|View full text |Cite
|
Sign up to set email alerts
|

Product diversion by vertically differentiated firms

Abstract: Retail sellers authorized to sell a branded product may divert some units to an unauthorized dealer thus enabling the dealer to become a direct competitor. Because these sellers vary in quality, it is often unclear what type of seller is more motivated to participate in diversion. We develop an analytical model to demonstrate how vertically differentiated sellers make diversion decisions responding to an unauthorized dealer under unique circumstances not considered by previous research. The model demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Though a few studies have examined the launch of the upgraded version of products in the durable goods industry (e.g., Xiong et al, 2016), the impact of the manufacturer's product upgrade decision on supply chain members in the presence unauthorized gray market selling is completely unexplored. It is observed that such a decision increases the risk of product diversion to the gray market (Smith & Shulman, 2022). This is because the decision of launching an upgraded product pressurizes the retailer to clear the unsold stock of the earlier version of the product to avoid the risk of low salvage value at the end of season.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though a few studies have examined the launch of the upgraded version of products in the durable goods industry (e.g., Xiong et al, 2016), the impact of the manufacturer's product upgrade decision on supply chain members in the presence unauthorized gray market selling is completely unexplored. It is observed that such a decision increases the risk of product diversion to the gray market (Smith & Shulman, 2022). This is because the decision of launching an upgraded product pressurizes the retailer to clear the unsold stock of the earlier version of the product to avoid the risk of low salvage value at the end of season.…”
Section: Discussionmentioning
confidence: 99%
“…However, assumptions of extant supply chain mechanisms deliberated are quite static in terms of their consideration of dynamic aspects, such as short product life cycle, launch of an upgraded version of the existing product, and the retailer's flexibility to adjust the price of the existing product during the selling season. Most importantly, regarding pricing, the extant research has assigned the authorized channel's price as unchanged during the selling season to curtail a realistic view (Smith & Shulman, 2022;Srivastava & Mateen, 2020). Therefore, given this insufficiency in the literature, we examine the viability of capitalizing on empowering the retailer with significant flexibility over pricing decisions to control gray market diversion based on domestic bootlegging.…”
Section: Brand(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Intuitively, when γ = 0, the MNF’s demand function reduces to the monopoly case. In the Online E-Companion H, we consider the Hotelling model, which is used in some gray market literature (e.g., Smith and Shulman, 2022), and find that main insights are qualitatively robust.…”
Section: Model Formulationmentioning
confidence: 99%